Arab human development in the twenty-first century : the primacy of empowerment - Korany, Bahgat (Cairo : American University in Cairo Press, 2014)
Human capital; Arab countries; social change; social and economic conditions; 21st century.
Includes bibliographical references (p. 353-378) and index.